Economic Consequences of Political Polarization: Evidence from an SEC Shutdown and Its Effect on Insider Trading - Bens, Daniel A.; Cassar, Gavin; Huang, Ying; Keusch, Thomas (The Accounting Review, 2026)
ABSTRACT We exploit a one-month period when SEC activity largely stopped during a U.S. government shutdown to examine whether variation in SEC scrutiny affects its ability to enforce insider trading. Difference-in-differences analyses suggest insiders earn abnormal profits during the shutdown, and the findings are robust to using different control periods and groups. We estimate that it takes roughly one week before the abnormally profitable trading begins, consistent with insiders updating their beliefs regarding the duration and disruption of the shutdown. Supporting the claim that SEC regulatory activity drops with the shutdown and does not fully recover afterward, we find a decline in the frequency of insider trading enforcement releases, investigations, and comment letter issuances after the SEC resumes operations. Our study speaks to the SEC insider trading enforcement literature and economic consequences of a regulatory discontinuity in a divisive political climate. Data Availability: All data are available from public sources. JEL Classifications: G14; G30; M41; M48.